CONSEQUENCES OF THE BRAND´S EXPERIENCE IN CONSUMERS OF SMARTPHONES SECTOR (Dimensión Empresarial, 2019)
The purpose of this work is to measure the influence of brand experience of users of smartphones and its consequence in relation to the brand loyalty. The data collection occurred through the use of social media and 570 valid questionnaires were obtained in more than 120 cities in Brazil. The data analysis occurred through the application of the techniques of multivariate data analysis. Of the eigth tested hypotheses, seven of them were supported. It was concluded that the brand experience significantly influences the brand personality, which also significantly influences the consumer satisfaction. In addition, the brand experience, the brand personality and the satisfaction influence the consumers loyalty, which has a value of approximately 60% for the explained variance. The formation of the constructs was also verified of a second level of experience of the brand and the brand personality.